Leaching behavior of chromium in chrome shaving generated in tanning process and its stabilization - Erdem, Mehmet; Ozverdi, Arzu (Elsevier, 2008)
In this study, leaching properties and pollution potential of chromium in chrome shaving (CS), which is a solid residue of leather industry, containing 2.27% Cr were investigated and thermal stabilization procedure was applied to the CS for chromium immobilization. For this purpose, firstly, effects of the liquid/solid ratio, contact time, pH and sequential extraction on the leaching behavior of chromium in the CS were studied. It was determined that the CS-caused chromium pollution is a hazardous material for environment. Thermal stabilization procedure was applied to the CS in the temperature range of 250-500 degrees C for the chromium immobilization. Effective stabilization of chromium in the CS was achieved by heating of CS at 350 degrees C under CO2 atmosphere. Leaching experiments were also carried out with the samples obtained from the stabilization process and the results compared with that of the CS. Also, TCLP test method was applied to the samples to determine pollution potentials and discharge situations of the CS and its stabilization products. While the chromium concentrations in the test solutions of all samples stabilized thermally at above 350 degrees C were below the USEPA regulatory limit of 5 mg/l, the concentration of chromium leached out from the CS was 30-fold bigger than the USEPA regulatory limit. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: chromium; thermal stabilization; tanning waste; chrome shaving; leather processing